Efeito inibitório de diferentes concentrações de nisina sobre Staphylococcus aureus em queijo minas frescal - Bruna Amaral Felício (2012)
The use of nisin in food has been the object of several studies, dairy products included. The main objective of this research was to evaluate the antagonistic effect the addition of different nisin doses had on Staphylococcus aureus in Minas Frescal cheese during 30 days after being made. A preliminary in vitro test was carried out with four nisin doses, 100, 200, 400 and 500 IU/mL, to assess the effect on the multiplication of S. aureus in reconstituted nonfat milk at 10% (RNM 10%). By the data obtained at this stage, nisin concentrations of 400 and 500 IU/mL were selected to be tested on Minas Frescal cheese. Those concentrations presented higher inhibition potential against in vitro S. aureus. During the cheese manufacture process, a S. aureus ATCC 6538 culture was added in a sufficient amount so that the initial concentration would reach approximately 106 CFU/mL, and nisin concentrations of 400 and 500 IU/mL. Samples of milk, whey, curd and cheese on the first, seventh, fourteenth and thirtieth day after being made were analyzed. The results showed that nisin in 500 IU/mL provided lower counts of S. aureus in cheese, demonstrating a better bactericidal effect than the 400 IU/mL dose. The use of nisin was effective for the initial reduction of S. aureus and for maintaining its lower counts in Minas Frescal cheese during during 30 days after being made.